PELANGGARAN HAK ASASI MANUSIA DALAM KEBIJAKAN DAERAH DI BIDANG TATA RUANG DI KABUPATEN KUNINGAN - Haris Budiman (Universitas Kuningan, 2017)
Guarantee legal certainty and economic stability is very important to keep the movement of the economy of a country. The formulation of the problem formulated a point of issue is how the environmental law enforcement in Indonesia on a case study of forest fires in Indonesia and How to influence environmental law enforcement to economic growth in Indonesia. The purpose of this study was to determine the environmental law enforcement in Indonesia on a case study of forest fires in Indonesia and How to influence environmental law enforcement to economic growth in Indonesia. This research could be useful in a practical and theoretical. The method used by the researchers are using a normative juridical approach. The results of the study Enforcement of Environmental Law in relation to the Criminal Law which is related substance of Law in Article 69 paragraph (1) letter H Law No. 32 of 2009 on the Protection and Environmental Management includes about a ban on land clearing by burning and action against the perpetrators for enforce the law and environmental law enforcement to economic growth in Indonesia affected by three (3) aspects, namely Products of law, justice system and political risks are always changing. Conclusions of law enforcement carried out by the legislation in force and the factors that influence economic growth is necessary to be noticed is the commitment of the highest officials responsible to the reciprocation of a country. Recommendation law enforcement must be carried out according the legislation without seeing the background of the company or individual that legal certainty to invest guaranteed and the reformulation of Article 69 paragraph (1) letter H Law No. 32 of 2009 on the Protection and Environmental Management.